IMMUNOCHROMATOGRAPHIC ANALYSIS FOR THE DETECTION OF ANTIBODIES AGAINST THE BOVINE LEUKEMIA VIRUS - Tursunov , K.; Raiymbek , G.; Shustov , A.V.; Begalieva , A.; Іnіrbay B.; Sadiknabi , I.; Mukanov , K.K.; Ramanculov , E.M.; Mukantayev , K.N. (Eurasian Journal of Applied Biotechnology, 2015)
Bovine leukemia is an important infectious diseasethat affects farm animals. The viral etiology of the disease is well recognized. The disease causes significant economic damage to agricultural enterprises, including losses associated with the death and premature culling of high producing cows, reduced productivity, reduced milk quality, the cost of anti-leukemic measures. All these factors endanger the preservation of breeding herds, and threaten the management and breeding efforts to improve productive traits in dairy cattle. In the present study, we determined that the optimal concentration of recombinant gp51 antigen to immobilize on a nitrocellulose membrane is 500 µg/ml. For the preparation of a colloidal gold conjugate, the optimal concentration of protein G is 8 µg/ml. The amount of colloidal gold conjugate for the membrane was 7 µl per 1 strip. We found that the diagnostic characteristics of the immunochromatographic assay clearly differentiate the positive control sera of infected animals from sera of healthy animals, and also differentiates between serum samples with brucellosis and FMD. When determining the sensitivity of the test system, specific antibodies in the positive control sera were detected at a dilution of 1:1600. Comparison of 145 positive serum samples in a lateral flow assay with immunoenzyme analysis and reaction immunodiffusion showed 97% agreement between the results.